Comparison of pulp necrosis and root gangrene cases at the Dental Clinic of the Baturiti II Community Health Centre in Tabanan: Comparison of pulp necrosis and root gangrene cases at the Dental Clinic of the Baturiti II Community Health Centre in Tabanan - Putri, Kadek Adisty Maharani; Idaryati, Ni Putu; Ariani, Ni Luh Putu (Makassar Dental Journal PDGI Makassar, 2025)
Untreated dental caries can progress to pulp necrosis and subsequently to root gangren; both conditions have the potential to cause infection if left untreated. This study compared the prevalence of pulp necrosis and root gangrene cases based on gender and age at the Baturiti II Tabanan Community Health Centre during January-March 2025. A quantitative descriptive method was used with purposive sampling techniques on secondary data from the e-puskesmas system. The prevalence of root gang-rene (7.2%) was higher than that of pulp necrosis (5.9%). Female patients dominated in both cases, accounting for 52.7% of pulp necrosis cases and 56.5% of root gangrene cases. The 20-44 age group was the most common for pulp necrosis (42.1%), while root gangrene was most common in the 45-59 age group (34.8%). This indicates delayed dental care contributing to di-sease progression. Low levels of public knowledge and behavioural factors also contribute to the high incidence rates. It is con-cluded that there is a need to improve communication, information, and education regarding oral health, particularly at the pri-mary healthcare facility level.